2023
DOI: 10.1111/epi.17532
|View full text |Cite
|
Sign up to set email alerts
|

Influence of comorbidity on mortality in patients with epilepsy and psychogenic nonepileptic seizures

Abstract: Objective This study aims to determine the contribution of comorbidities to excess psychogenic nonepileptic seizures (PNES) mortality. Methods A retrospective cohort study was conducted of tertiary epilepsy outpatients from St. Vincent's Hospital Melbourne, Australia with an 8:1 comparison cohort, matched by age, sex, and socioeconomic status (SES) to national administrative databases between 2007 and 2017. Privacy‐preserving data linkage was undertaken with the national prescription, National Death Index, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A study by Tan et al [21 ▪▪ ] replicated the high HR of premature death in people diagnosed with PNES but concluded that, unlike in those with epilepsy, the excess mortality in the PNES cohort was fully explained by increased rates of comorbidities. Psychotic illness, opioid analgesia, malignancies, and nonopioid analgesia had the greatest influence on PNES mortality.…”
Section: Comorbidities and Mortalitymentioning
confidence: 99%
“…A study by Tan et al [21 ▪▪ ] replicated the high HR of premature death in people diagnosed with PNES but concluded that, unlike in those with epilepsy, the excess mortality in the PNES cohort was fully explained by increased rates of comorbidities. Psychotic illness, opioid analgesia, malignancies, and nonopioid analgesia had the greatest influence on PNES mortality.…”
Section: Comorbidities and Mortalitymentioning
confidence: 99%